Polypoidal Choroidal Vasculopathy - Huddleston, Amy; Phan, Tyler; Tucker, Tiffany (Canadian Journal of Optometry, 2018)
Polypoidal choroidal vasculopathy (PCV) is a disease of the choroidal vasculature that may result in sub-retinal hemorrhage and serous detachment of the retinal pigmented epithelium (RPE), leading to sub-retinal brosis and, sometimes, permanent vision loss. This report describes a case of PCV in an African-American female over the course of 1 year and demonstrates the progression of PCV, from being relatively asymptomatic to the development of a visually significant sub-retinal hemorrhage. She is currently being treated with Avastin intravitreal injections with some resolution of her symptoms and a reduction of sub-retinal bleeding.